Bacteriologic, Serologic and Pathologic Studies on Abortus Cases of Goats and Sheep in Elazi? and it's Vicinity - Muz, Adile; Ertaş, Hasan Basri; Öngör, Hasan; Gülcü, Hasan Basri; Özer, Harun; Eröksüz, Hatice; Kalender, Hakan (My University, 1999)
In this study, the etiology of ovine and caprine abortions was investigated bacteriologically, serologically and pathologically. Tissue samples collected from aborted sheep and goats in Elazi? and its borders were examined bacteriologically and pathologically for brucellosis, campylobacteriosis, salmonellosis and listeriosis. In addition, blood samples collected from aborted sheep and goats were examined by serological tests for the presence of antibodies to these bacteria. Of 110 aborted fetuses, in 22 (20%) Brucella melitensis, in 5 (4.5%) Campylobacter fetus subsp. fetus, in 4 (3.6%) Salmonella abortus ovis, in 1 (0.9%) Listeria monocytogenes and in 3 (2.7%) E. coli were isolated and identified. In the serological examination of 650 sheep and goat blood samples, antibodies were detected in 77 (11.8%) to brucella, 13 (2.0%) to compylobacter and to salmonella in 13 (2.0%) to salmonella, but these sera were found negative for listeria. Edema in subcutaneous connective tissues, the accumulation of hemorrhagic fluid in the thorax and abdomen, and a yellowish, cloudy coagulated mass in the abomasum were the macroscopic lesions observed in the infected fetuses. In the microscopic analysis, hemorrhage in the lungs and the liver, degeneration and necrosis, mononuclear cell infiltration and diffuse tubulo-interstitial hemorrhage in the kidneys were observed.
Elazi? ve Çevresinde Koyun ve Keçilerde Abortus Olgularinin Bakteriyolojik, Serolojik ve Patolojik Olarak İncelenmesi
Keywords: Abortion; Bacterial agents; Elazi?; Goat; Sheep